1998
DOI: 10.1021/bi980573c
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Loss of β2-Microglobulin Expression in Drug-Resistant Breast Cancer Sublines and Its Involvement in Drug Resistance

Abstract: In this study, we investigated the mechanism of the loss or decreased expression of beta 2-microglobulin (beta 2m) in several drug-resistant sublines of MCF-7 and in a doxorubicin (DOX)-resistant variant of the T-47D breast cancer cell line. beta 2m protein and RNA are not expressed in highly metastatic, multidrug-resistant MCF-7/Adr cells with high resistance to DOX. Nuclear run-on transcription and RNA stability assays demonstrate that while beta 2m in MCF-7/Adr cells is transcribed, its mRNA is rapidly degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 35 publications
(55 reference statements)
1
33
0
Order By: Relevance
“…These results suggest that b 2 m may utilize an apoptosis pathway distinct from Class I MHC antigen complexinduced apoptosis (Genestier et al, 1997a,b;WallenOhman et al, 1997). The decreased expression levels of b 2 m in HL-60 drug resistant variants con®rms our previous report demonstrating that the loss of b 2 m expression in breast cancer cells is associated with resistance to DOX, and that inhibition of its expression in MCF-7 cells by an antisense b 2 m expression vector induced the drug resistance phenotype (Ogretmen et al, 1998). Partial or complete loss of b 2 m in several aggressive metastatic cancers or cell lines derived from such cancers has been observed (Kakamanis et al, 1995;Vitale et al, 1998;Restifo et al, 1993;Benitez et al, 1998).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results suggest that b 2 m may utilize an apoptosis pathway distinct from Class I MHC antigen complexinduced apoptosis (Genestier et al, 1997a,b;WallenOhman et al, 1997). The decreased expression levels of b 2 m in HL-60 drug resistant variants con®rms our previous report demonstrating that the loss of b 2 m expression in breast cancer cells is associated with resistance to DOX, and that inhibition of its expression in MCF-7 cells by an antisense b 2 m expression vector induced the drug resistance phenotype (Ogretmen et al, 1998). Partial or complete loss of b 2 m in several aggressive metastatic cancers or cell lines derived from such cancers has been observed (Kakamanis et al, 1995;Vitale et al, 1998;Restifo et al, 1993;Benitez et al, 1998).…”
Section: Discussionsupporting
confidence: 88%
“…We previously reported that the loss or decreased expression of b 2 m results in drug resistance in sublines of MCF-7 cells selected for resistance to the chemotherapeutic agent doxorubicin (DOX), and in a DOX-resistant variant of the T-47D human breast cancer cell line (Ogretmen et al, 1998). These data suggested that the loss of b 2 m in cancer cells may cause both resistance to chemotherapy as well as an escape from immune surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Semiquantitative reverse transcriptase-PCR (RT-PCR) protocols that compare relative transcript levels of target genes with those of housekeeping genes (including 16S or 18S rRNA) also use the internal control to titrate the exact amount of total RNA added to each reaction (Nicoletti and SassyPrigent, 1996;Ogretmen et al, 1998;Wang et al, 2002). The expression of N-regulated genes, ntcA, napA and nifH, was studied using this semiquantitative RT-PCR method with minor modifications.…”
Section: Rt-pcrmentioning
confidence: 99%
“…Nuclear run-on analysis was performed as previously described (Ogretmen et al, 1998). Briefly, nuclei from HL-60, HL-60/ADR cells were isolated and stored in 100 ml of freezing buffer (50 mM Tris-HCl, pH 8.3, 40% glycerol, 5 mM MgCl 2 and 0.1 mM EDTA).…”
Section: Nuclear Run-on Transcription Assaymentioning
confidence: 99%
“…Equal counts of TCA-precipitated labeled transcripts were used for hybridizations of slot blots containing 0.4 mg 360 bp human PR3 and 1.8 kb human b-actin (CloneTech, Palo Alto, CA, USA) cDNA fragments. Hybridizations were performed at 458C for 72 -96 h and then filters were washed at 578C with 26SSC -1% SDS and 0.16SSC -1% SDS for 1 -2 h as we previously described (Ogretmen et al, 1998). Bands were visualized by autoradiography at -808C for 7 -10 days, and quantitated by densitometry using Photoshop version 4 software.…”
Section: Nuclear Run-on Transcription Assaymentioning
confidence: 99%